2014
DOI: 10.2147/cia.s65921
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α gene polymorphisms and risk of Alzheimer’s disease: evidence from a meta-analysis

Abstract: ObjectiveHuman estrogen receptor α (ESR1), a member of the nuclear receptor superfamily of ligand-activated transcription factors, is one of the key mediators of hormonal response in estrogen-sensitive tissues. Accumulating evidence has demonstrated that two of the most widely studied single-nucleotide polymorphisms in ESR1 – PvuII (T/C, rs223493) and Xbal (A/G, rs9340799) – are possibly associated with Alzheimer’s disease (AD). However, individual study results are still controversial.Materials and methodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
(46 reference statements)
3
22
0
Order By: Relevance
“…Similar to previous findings, no association was found between AD and rs2234693 in this Chinese population. This finding is also consistent with a recent meta‐analysis that found the rs2234693 was associated with risk of AD in Caucasian but not in Asian populations . The putative role of the CYP19A1 gene in the development of AD has been investigated in several studies that yielded inconsistent results in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to previous findings, no association was found between AD and rs2234693 in this Chinese population. This finding is also consistent with a recent meta‐analysis that found the rs2234693 was associated with risk of AD in Caucasian but not in Asian populations . The putative role of the CYP19A1 gene in the development of AD has been investigated in several studies that yielded inconsistent results in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is also consistent with a recent meta-analysis that found the rs2234693 was associated with risk of AD in Caucasian but not in Asian populations. 46 The putative role of the CYP19A1 gene in the development of AD has been investigated in several studies that yielded inconsistent results in Caucasians. A significant association was found between CYP19A1 and AD in a study with a small sample size, 28 whereas data from genome-wide association studies with larger sample sizes conducted in Canada 22 and the United States 47 have not found such an association.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor 1 (ESR1) is an essential member of the nuclear hormone receptor super family and serves as a ligand-activated transcription factor composed of several domains important for DNA binding, hormone binding, and transcription activation (Cheng et al, 2014). ESR1 is mainly expressed in macrophages, endothelial cells, and vascular smooth muscle cells, and it plays an important role in vascular wall physiology and function (Gao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some hypotheses for the functional significance of this polymorphism shall be discussed. Cheng et al 14 reported that ERS-1 polymorphisms might influence the gene expression and affect estrogen function. Given its location, 351 bp upstream from the start of exon 2, a mechanism including changes on ESR-1 expression via altered binding of transcription factors and influence on alternative splicing of the ESR-1 gene has been suggested 15 .…”
Section: Discussionmentioning
confidence: 99%